Wage convergence and trade - Zhou, Yixiao; Bloch, Harry (Wiley-Blackwell Publishing, 2019)
We examine differences in wage rates across countries for workers employed in the same industry, distinguishing workers in the low, medium and high-skill groups. These differences are large and show persistence over time. We ask, nonetheless, whether there is evidence of convergence, much as is done in studies of convergence in per capita income across countries. With our focus on the micro level, we expect convergence to reflect, at least in part, the degree of integration of a country or industry into the world economy and examine particularly the role of market integration and trade. Our results show strong evidence of convergence in a diverse sample of 39 countries, which includes most large economies whether rich or poor. The estimated convergence rate over the period from 1995 to 2008 is about 4% per year for workers in all skill groups, higher in the more integrated economies of the EU than in other economies without such open borders and lower in industries supplying services rather than manufactures. Also, we find evidence that the rate of growth of domestic output impacts positively on the growth of wages in an industry, providing a source for ongoing deviations from the convergence prediction.